2015
DOI: 10.1097/fjc.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FGFR Signaling With PD173074 Ameliorates Monocrotaline-induced Pulmonary Arterial Hypertension and Rescues BMPR-II Expression

Abstract: These results suggest that PD173074 can alleviate monocrotaline-induced pulmonary arterial hypertension and it may be a useful option for PAH. Our data also suggest a role of FGF-2/bone morphogenetic protein signaling interaction in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…). Pharmacological inhibition of FGF signaling attenuates monocrotaline‐induced PH and rescues bone morphogenetic protein receptor II ( BMPR‐II ) expression (Zheng et al, ). Receptor tyrosine kinase (RTK) inhibitors such as suramin, ponatinib, and imatinib also result in beneficial effects in experimental PH (Izikki et al, ; Kang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…). Pharmacological inhibition of FGF signaling attenuates monocrotaline‐induced PH and rescues bone morphogenetic protein receptor II ( BMPR‐II ) expression (Zheng et al, ). Receptor tyrosine kinase (RTK) inhibitors such as suramin, ponatinib, and imatinib also result in beneficial effects in experimental PH (Izikki et al, ; Kang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because increased PA pressures cause the pulmonary valve to close prematurely and decrease the PAT and PAT/ET ratio, our findings suggest that hyperoxia-induces a PH phenotype, and this phenotype is augmented by endothelial ERK2 deficiency in neonatal mice. Interventions used to rescue the PH phenotype in adult rodents decrease ERK1/2 activation [63][64][65][66], suggesting that activation of these kinases promotes the development of PH. Similarly, Young et al [67] demonstrated that inhibition of c-kit signaling mitigates hypoxia-induced PH in neonatal mice by downregulating activation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…We found that TGF-betaR1 and smad4 were possible downstream targets of miR-140-5p, reduction in miR-140-5p in PAH might stimulate TGF-beta1/Smad4 pathway by upregulating TGF-betaR1 and smad4. Previous studies have demonstrated that PDGF, TLR4, VEGFA, and FGF contribute to the pathogenesis of PAH via activating various signaling pathways, especially PI3K/Akt cascade [24][25][26][27][28]. CREB, an important transcription factor lying downstream of PI3K/Akt pathway, mediates the partial functions of PI3K/Akt [29].…”
Section: Discussionmentioning
confidence: 99%